Ectopic expression of Nav1.7 in spinal dorsal horn neurons induced by NGF contributes to neuropathic pain in a mouse spinal cord injury model - Fu, Yan; Sun, Liting; Zhu, Fengting; Xia, Wei; Wen, Ting; Xia, Ruilong; Yu, Xin; Xu, Dan; Peng, Changgeng (Frontiers in Molecular Neuroscience, 2023)
Neuropathic pain (NP) induced by spinal cord injury (SCI) often disturbs the life of patients for lifelong. Uncovering the mechanisms underlying SCI-induced NP will help to develop drugs for this chronic pain treatments. Here our study showed that SCI-induced ectopic expression of Nav1.7 in abundant neurons located in deep and superficial laminae layers of spinal dorsal horn (SDH) and up-regulation of Nav1.7 expression in dorsal root ganglion (DRG) neurons in mice. Pharmacologic studies demonstrated that the efficacy of blood-brain-barrier (BBB) permeable Nav1.7 inhibitor GNE-0439 for attenuation of NP in SCI mice was significantly better than that of BBB non-permeable Nav1.7 inhibitor PF-05089771, and GNE-0439 had equivalent efficacy to Gabapentin and without sedation side effects. More than 20% Nav1.7-expressing SDH neurons in SCI mice were activated to express FOS when there were no external stimuli, suggesting that the ectopic expression of Nav1.7 made SDH neurons hypersensitive and Nav1.7-expressing SDH neurons participated in central sensitization and in spontaneous pain and/or walking evoked mechanical pain. Further investigation showed that NGF, a strong activator of Nav1.7 expression, was upregulated after SCI in SDH neurons with similar distribution pattern and in DRG neurons too. In conclusion, our findings showed that the upregulation of Nav1.7 was induced by SCI in both SDH and DRG neurons through increased expression of NGF, and the inhibition of Nav1.7 in both peripheral and spinal neurons alleviated mechanical pain in SCI mice. These data suggest that BBB permeable Nav1.7 blocker could efficiently relieve NP in patients with SCI and blocking the up-regulation of Nav1.7 in early stage of SCI via selective inhibition of the downstream signal pathway of NGF or Nav1.7-targeted RNA drugs could be a strategy for therapy of SCI-induced NP.